The London Art of Plagiarism, Part Two - Lucraft, Fiona (Petits Propos Culinaires, 1993)
In PPC 42 we published the first part of a major essay by Fiona Lucraft on the sources used by the 18th century cookbook writer, John Farley. It emerged from this that virtually all his book was taken from two famous books by women writers, Hannah Glasse and Elizabeth Raffald, whose books had first been published in 1747 and I 769 respectively. We promised to follow up this startling exposure with an account of Farley’s use of minor sources.